Pembelajaran Menulis Kalimat Poster Menggunakan Metode Inkuiri di Madrasah Tsanawiyah - Maya Bangun Palinda (Jurnal Guru Indonesia, 2021)
This research is motivated by the low writing ability of students, especially in writing poster sentences. In fact, at present, there are still many students at MTs Daarul Uluum PUI Majalengka who have not been able to write poster sentences correctly. In addition to the formulation of the problem, this study also has a purpose. The objectives of this study are as follows. 1) Obtain data about the ability of class VIII students of MTs Daarul Uluum PUI Majalengka in writing poster sentences before learning using the inquiry method. 2) Obtain data about the ability of class VIII students of MTs Daarul Uluum PUI Majalengka in writing poster sentences after learning using the inquiry method. 3) Obtaining data about the effectiveness of using the inquiry method in learning to write poster sentences for class VIII students of MTs Daarul Uluum PUI Majalengka. The method used in this research is a descriptive method, while the techniques used are data collection techniques and data processing and analysis techniques. The population of the study was 5-grade students of MTs Daarul Uluum PUI Majalengka with a total population of 200 students. The sample in this study was 1 class, namely class VIII B with 35 students. The results of data processing and analysis showed the answer to the problem formulation, namely the results of the pretest students' ability in learning to write poster sentences was still low, only reaching 67.29%, but post-test results increased to 84.57%. With the level of effectiveness of using the inquiry method in learning to write poster sentences, it has a correlation of 0.464%, including the moderate categoryPenelitian ini dilatarbelakangi oleh masih rendahnya kemampuan menulis pada siswa, khususnya dalam penulisan kalimat poster. Kenyataannya pada saat ini masih banyak siswa MTs Daarul Uluum PUI Majalengka yang belum mampu menulis kalimat poster secara benar.Tujuan dalam penelitian ini adalah sebagai berikut. 1) Mendapatkan data mengenai kemampuan siswa kelas VIII MTs Daarul Uluum PUI Majalengka dalam menulis kalimat poster sebelum pembelajaran dengan menggunakan metode inkuiri. 2) Mendapatkan data mengenai kemampuan siswa kelas VIII MTs Daarul Uluum PUI Majalengka dalam menulis kalimat poster setelah pembelajaran dengan menggunakan metode inkuiri. 3) Mendapatkan data mengenai efektivitas penggunaan metode inkuiri dalam pembelajaran menulis kalimat poster siswa kelas VIII MTs Daarul Uluum PUI Majalengka Metode yang digunakan dalam penelitian ini adalah metode deskriptif sedangkan teknik yang digunakan yaitu teknik pengumpulan data serta teknik pengolahan dan analisis data. Populasi penelitian adalah siswa kelas VIII MTs Daarul Uluum PUI Majalengka sebanyak 5 kelas dengan jumlah populasi 200 siswa. Sampel dalam penelitian ini adalah 1 kelas yaitu kelas VIII B dengan jumlah siswa 35 orang. Hasil dari pengolahan dan analisis data menunjukkan jawaban terhadap rumusan masalah yaitu hasil pretes kemampuan siswa dalam pembelajaran menulis kalimat poster masih rendah hanya mencapai 67,29%, tetapi hasil postes terdapat peningkatan menjadi 84,57%. Dengan tingkat efektivitas penggunaan metode inkuiri dalam pembelajaran menulis kalimat poster memiliki korelasi 0,464% termasuk kategori sedang.